Comparison of Indonesian Airspace Security Regulations with the United States as Representatives of Legal Reform - Rosari, Uli; Daulay, Zainul; Mulyati, Nani (Journal of Law, Politic and Humanities, 2025)
Airspace is a crucial aspect of state sovereignty that must be protected through legal means. However, Indonesia lacks specific and comprehensive regulations governing airspace violations by foreign aircraft, both civil and military. Existing laws, Law No. 1/2009, Government Regulation No. 4/2018, and SKEP/195/IX/2008 are limited to administrative procedures without clear mechanisms for enforcement, violation classification, or proportional sanctions. This research aims to analyze the weaknesses in current regulations and emphasize the urgency of forming new legal frameworks as part of national legal reform. Using a normative juridical method with a conceptual and comparative approach, particularly with the United States, this study draws on the theories of state sovereignty, legal politics, law enforcement, and psychological coercion. The findings reveal that Indonesia’s legal framework suffers from the absence of ADIZ regulation, lack of operational enforcement procedures, weak penalties, and limited coordination between civil and military authorities. Therefore, a new regulation that is assertive, integrative, and responsive is urgently needed to uphold airspace sovereignty and strengthen Indonesia's legal capacity in safeguarding national airspace.